Hafez's Linguistic and Semantic Tricks with the Names of Slaves and Maids in Making Amphibology of Proportion - Salimi, Hossein (LANGUAGE ART, 2021)
Hafez's poetry can be considered the most complex and mysterious poem in Persian in terms of using the capacities and artistic, rhetorical and semantic functions of language. In this regard, he goes so far as to say that in order to receive and understand the intellectual world of his speech, no part of his speech can be ignored and delayed. He has cleverly and consciously used all the subtleties and capacities of language to express his thoughts and draw his worldview, and he has benefited from them with all his skill... One of these linguistic features is the names of a kind of slaves and maids in different historical periods of Iran that were given to them for different reasons. It is because of the use of these linguistic tricks that Hafez's poetry has always been studied by literary scholars from various angles... On the other hand, since the most important stylistic and artistic feature of Hafiz is his astonishing use of ambiguity and its types, and especially the ambiguity of proportions, many scholars and poets have tried to extract the evidence of ambiguity and Its variants in his poetry show the different layers of semantics and linguistic mystery of his art and reveal the wonders of the prismatic relations of words in his poetry. In this research, an attempt has been made to show the artistic applications of the names of a kind of slaves and maids in the construction of proportionality and ambiguity in Hafez's poetry through documentary and analytical methods. The results of the research show that Hafez, consciously and prudently, uses the names of a kind of slaves and maids in a context of ambiguity and confusion in order to make the prismatic and engineered relations of his poetic words more artistic. And to convey his political and social ideas to the audience in indirect and multi-layered language.